Journal of Evidenced-Based Psychotherapies, Vol. 22, No. 1/2022 - DAVID, Oana Alexandra (2022)
Journal of Evidence-Based Psychotherapies is the successor of the Journal of Cognitive and Behavioral Psychotherapies (2001-2013) and is published biannually (in March and September) in one volume per year by the International Institute for the Advanced Studies of Psychotherapy and Applied Mental Health. The journal is devoted to the advancement of the clinical theory and practice of evidence-based psychotherapies (EBP) (e.g. evidence-based psychological assessments, evidence-based psychological treatments). The journal publishes original papers dealing with EBP and psychology, psychiatry, the medical and mental specialties, and allied areas of science. Submissions include (1) articles referring to clinical and experimental studies, discussions of theory, and systematic reviews for inclusion in Article Section, (2) articles referring to clinical discussions/developments for inclusion in the Clinical Forum Section, and (3) commentaries, letters to the editor, reviews and abstracts of books, tapes, and films, salient findings in EBP, and other information relevant to the journal''''''''s goal for inclusion in the Development and Resources Section. Finally, the journal seeks to publish special issues devoted to topics of particular interest, suggestions for which are welcomed by the Editor.